ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI IKAN MAS KERAMBA DI DESA KOTO MESJID KECAMATAN XIII KOTO KAMPAR KABUPATEN KAMPAR PROVINSI RIAU - Boy Pardamean Manullang; Khairizal; Azharuddin M. Amin; Khairudin (UIR Press, 2023)
In Koto Masjid Village, District XIII Koto Kampar, there are several potential cage carp farms that have not been able to achieve optimal production results. The purpose of this study is to analyze the influence of production factors on carp farming production in the XIII Koto Kampar sub-district. This research used a survey method, which was carried out in Koto Village, Mosque, and XIII Koto Kampar sub-district from August 2021 to January 2022. The number of samples taken was 30 carp farmers who were taken randomly (simple random sampling). The data analysis used in this study was qualitative and quantitative descriptive analyses, as well as multiple regression analysis using the Cobb-Douglass production function method. The results showed that the factors that had a significant effect on carp production were variable cage area and amount of feed, with a significance level of 5%.